How osteogenic is dexamethasone?—effect of the corticosteroid on the osteogenesis, extracellular matrix, and secretion of osteoclastogenic factors of jaw periosteum-derived mesenchymal stem/stromal cells - Umrath, Felix; Pfeifer, Achim; Cen, Wanjing; Danalache, Marina; Reinert, Siegmar; Alexander, Dorothea; Naros, Andreas (Frontiers in Cell and Developmental Biology, 2022)
Dexamethasone (dexa) is commonly used to stimulate osteogenic differentiation of mesenchymal stem/stromal cells (MSCs) in vitro. However, it is paradoxical that glucocorticoids (GCs) like dexa lead to bone loss and increased fracture risk in patients undergoing glucocorticoid therapy, causing glucocorticoid induced osteoporosis (GIOP). In a recent publication we demonstrated, that osteogenic differentiation of progenitor cells isolated from jaw periosteal tissue (JPCs) is not depending on dexa, if the medium is supplemented with human platelet lysate (hPL) instead of fetal bovine serum (FBS). This allows the in vitro conditions to be much closer to the natural situation in vivo, and enables us to compare osteogenic differentiation with and without dexa. In the present study we demonstrate, that the absence of dexa did not reduce mineralization capacity, but instead slightly improved osteogenic differentiation of JPCs. On the other hand, we show that dexa supplementation strongly alters gene expression, extracellular matrix (ECM) and cellular communication of JPCs. Secretome of periosteal cells previously treated with osteogenic medium with and without dexa was used to investigate the changes in paracrine secretion caused by dexa. Dexa altered the secretion of several cytokines by JPCs and strongly induced osteoclast differentiation of peripheral blood mononuclear cells (PBMCs). This study demonstrates how dexa supplementation can influence the outcome of in vitro studies and highlights a possible role of periosteal cells in the pathogenesis of GIOP. The methods used here can serve as a model for studying bone formation, fracture healing and various pathological conditions such as (glucocorticoid-induced) osteoporosis, osteoarthritis, bone cancer, and others, in which the interactions of osteoblasts with surrounding cells play a key role.